THE RELEVANCE OF THE CONTENT OF RELIGIOUS EDUCATION TEACHING MATERIALS IN THE FAI UMSU ISLAMIC RELIGIOUS EDUCATION STUDY PROGRAM TO THE CONTENT OF AL-ISLAM SUBJECTS IN MUHAMMADIYAH MIDDLE SCHOOLS - Nurzannah, Nurzannah; Pasaribu, Munawir; Hasanuddin, Hasanuddin (Proceeding International Seminar of Islamic Studies, 2024)
This research aims: 1) Find out the contents of the Religious Education Courses in the PAI FAI UMSU Study Program, 2) Know the Contents of the Al-Islam Subjects at Muhammadiyah Middle Schools in Medan City, and 3) Describe the relevance of the Contents of the Religious Education Courses in the PAI UMSU Study Program to the content needs Al-Islam Subjects for Muhammadiyah Middle Schools in Medan City. This type of research is qualitative, using interview methods, content analysis, and Focus Group Discussion (FGD). The results of the research show that: 1) The contents of the Religious Education Courses in the PAI UMSU Study Program consist of the Al-Quran as a guide to life and relevant matters regarding the Al-Quran, Human Nature, Aqidah, Tauhid, Pillars of Faith, Things that Damage Faith, and Modern Shirk. 2) The content of Al-Islam subjects at Muhammadiyah Middle Schools in Medan City varies greatly. Because the books that are the source of learning differ from one school to another. 3) The relevance of the content of Islamic Education Study Program religious education courses to the content of Al-Islam subjects at Muhammadiyah Middle Schools in Medan is on average 65.5%. However, the deficiency in the content of the al-Islam subject in question can be supplemented by other courses that are taught to students at the PAI UMSU Study Program, including the courses Tahsin Al-Quran, History of Islamic Civilization, Insya' Muhadatsah, Tarbawi Tafsir and Hadith, Ushul Fiqh, and Contemporary Fiqh.